2012
DOI: 10.1158/1055-9965.epi-11-0727
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Clinical Role of Genetic Markers of Early-Onset Prostate Cancer among High-Risk Men Enrolled in Prostate Cancer Early Detection

Abstract: Background Men with familial prostate cancer (PCA) and African American men are at risk for developing PCA at younger ages. Genetic markers predicting early-onset PCA may provide clinically useful information to guide screening strategies for high-risk men. We evaluated clinical information from six polymorphisms associated with early-onset PCA in a longitudinal cohort of high-risk men enrolled in PCA early detection with significant African American participation. Methods Eligibility criteria include ages 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…A recent study in the largest HIV cohort in North America found that while age at prostate cancer diagnosis was younger among HIV-infected subjects, the difference was not statistically significant (21); findings were inconclusive with respect to young-onset prostate cancer in groups by HIV status because age was examined in 10-year bins rather than comparing age of young-onset prostate cancer cases by HIV status. Young-onset prostate cancers diagnosed before age 55 are biologically and genetically distinct compared to prostate cancers diagnosed in older men (8, 22). Moreover, high-grade prostate cancers occurring before age 55 have a higher risk of cancer-specific mortality (23).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study in the largest HIV cohort in North America found that while age at prostate cancer diagnosis was younger among HIV-infected subjects, the difference was not statistically significant (21); findings were inconclusive with respect to young-onset prostate cancer in groups by HIV status because age was examined in 10-year bins rather than comparing age of young-onset prostate cancer cases by HIV status. Young-onset prostate cancers diagnosed before age 55 are biologically and genetically distinct compared to prostate cancers diagnosed in older men (8, 22). Moreover, high-grade prostate cancers occurring before age 55 have a higher risk of cancer-specific mortality (23).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer presents some unique challenges in HIV-infected populations, including higher cancer-specific mortality rates in comparison to HIV-uninfected populations (3) and lower rates of prostate-specific antigen (PSA) screening in subpopulations, including racial and sexual minorities (46). Major established risk factors in the general population are older age, African American race, and family history of prostate cancer (7, 8); modifiable risk factors include androgen supplement use and obesity (9, 10). The influence of HIV-related factors on prostate cancer risk remains poorly defined (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a wealth of evidence implicating 8q24 variant alleles in the development of CaP; some of which state that there is a higher frequency amongst those of African ancestry [42] and with earlier time to prostate cancer [43]. There are several other CaP susceptibility loci identified through genome-wide association studies, with inconsistencies between ethnic groups [44].…”
Section: The Role Of Genetic and Biological Factorsmentioning
confidence: 99%